Graphene oxide decorated with zinc oxide nanoflower, silver and titanium dioxide nanoparticles: fabrication, characterization, DNA interaction, and antibacterial activity. Issue 7 (28th January 2019) - El-Shafai, Nagi; El-Khouly, Mohamed E.; El-Kemary, Maged; Ramadan, Mohamed; Eldesoukey, Ibrahim; Masoud, Mamdouh
Abstract : The fabrication, characterization, and antibacterial activity of novel nanocomposites based on graphene oxide (GO) nanosheets decorated with silver, titanium dioxide nanoparticles, and zinc oxide nanoflowers were examined. Abstract : The fabrication, characterization, and antibacterial activity of novel nanocomposites based on graphene oxide (GO) nanosheets decorated with silver, titanium dioxide nanoparticles, and zinc oxide nanoflowers were examined. The fabricated nanocomposites were characterized by various techniques including X-ray diffraction, ultraviolet-visible light absorption and fluorescence spectroscopy, Brunauer–Emmett–Teller theory analysis, Fourier transform infrared, and scanning electron microscopy. The antibacterial activity of the GO–metal oxide nanocomposites against two Gram-positive and two Gram-negative bacteria was examined by using the standard counting plate methodology. The results showed that the fabricated nanocomposites on the surface of GO could inhibit the growth of microbial adhered cells, and consequently prevent the process of biofilm formation in food packaging and medical devices. To confirm the antibacterial activity of the examined GO-nanocomposites, we examined their interactions with bovine serum albumin (BSA) and circulating tumor DNA (ctDNA) by steady-state fluorescence spectroscopy. Upon addition of different amounts of fabricated GO-nanocomposites, the fluorescence intensities of the singlet states of BSA and ctDNA were considerably quenched. The higher quenching was observed in the case of GO–Ag–TiO2 @ZnO nanocomposite compared with other control composites.